Should anger be encouraged in the classroom? - Yacek, Douglas (Technische Universität Dortmund, 2020)
In light of recent political developments in Western democracies, several political commentators and theorists have argued that encouraging anger in citizens may contribute to social justice and should therefore constitute an aim of civic education. In this article, Douglas Yacek investigates these claims in depth. In doing so, he expands on previous work on the political and educational significance of anger — particularly by critical and “agonistic” theorists of civic education — in two distinct ways. First, Yacek explores the psychological costs and benefits of cultivating student anger. Second, he examines the potential cultural effects of anger in Western democratic societies. While sympathetic to the defenses of anger that have been recently offered in political and educational theory, Yacek concludes that we should be cautious about embracing anger in civic education. In particular, he argues that anger involves serious psychological risk, may exacerbate the social problems that it sets out to solve, and can lead to a disposition of adversarial and politically counterproductive closed-mindedness. In the closing sections, Yacek suggests that experiences he calls “civic epiphanies” are central to cultivating a politically beneficial form of open-mindedness, and argues that such experiences should therefore be encouraged in civic education.
Political education, closed-mindedness and civic epiphany
Educational theory;Vol. 69. 2019, Issue 4, 421-437
Keywords: anger; political emotions; civic education; responsiveness; 370; politische Bildung; Wut; Bildungstheorie